Differences in social interaction- vs. cocaine reward in mouse vs. rat - Kummer, Kai K.; Hofhansel, Lena; Barwitz, Constanze M.; Schardl, Aurelia; Prast, Janine M.; Salti, Ahmad; El Rawas, Rana; Zernig, Gerald (Frontiers in Behavioral Neuroscience, 2014)
We previously developed rat experimental models based on the conditioned place preference (CPP) paradigm in which only four 15-min episodes of dyadic social interaction with a sex- and weight-matched male Sprague Dawley rat (1) reversed CPP from cocaine to social interaction despite continuing cocaine training, and (2) prevented the reacquisition/re-expression of cocaine CPP. In a concurrent conditioning schedule, pairing one compartment with social interaction and the other compartment with 15 mg/kg cocaine injections, rats spent the same amount of time in both compartments and the most rewarding sensory component of the composite stimulus social interaction was touch (taction). In the present study, we validated our experimental paradigm in C57BL/6 mice to investigate if our experimental paradigm may be useful for the considerable number of genetically modified mouse models. Only 71% of the tested mice developed place preference for social interaction, whereas 85% of the rats did. Accordingly, 29% of the mice developed conditioned place aversion to social interaction, whereas this was true for only 15% of the rats. In support of the lesser likelihood of mice to develop a preference for social interaction, the average amount of time spent in direct contact was 17% for mice vs 79% for rats. In animals that were concurrently conditioned for social interaction vs cocaine, the relative reward strength for cocaine was 300-fold higher in mice than in rats. Considering that human addicts regularly prefer drugs of abuse to drug-free social interaction, the present findings suggest that our experimental paradigm of concurrent CPP for cocaine vs social interaction is of even greater translational power if performed in C57BL/6 mice, the genetic background for most transgenic rodent models, than in rats.